PENGARUH KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA. (STUDI PADA RRI SEMARANG)â - Indah Wulandari, 11.42.02.0008 (Students Journal of Accounting and Banking, 2013)
The purpose of this study was to examine the influence of job characteristics and work environment on employee performance, job satisfaction with the mediation variable. The research was conducted at the RRI Semarang, respondents who used as many as 103 employees, instruments used in the study was a questionnaire. The method of data analysis using multiple regression analysis. Based on the analysis of this study concluded that the job characteristic has a positive effect on job satisfaction, work environment has a positive effect on job satisfaction, job characteristics has a positive effect on employee performance, work environment has a positive effect on employee performance, job satisfaction has positive effect on employee performance. The results also showed that job satisfaction is not a variable Â mediating influence between job characteristics on employee performance. Job satisfaction is not variable mediating influence between work environment on employee performance. But in total factor tends to further strengthen the work environment influence on the performance of employees through job satisfaction. Keywords: Â job characteristics, work environment, job satisfaction and employee performance.